2018
DOI: 10.1007/s10704-018-0303-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of plasticity and fracture behavior of X65 steels: seam weld and seamless pipes

Abstract: A non-associated/associated flow rule coupled with an anisotropic/isotropic quadratic yield function is presented to describe the mechanical responses of two distinct X65 pipeline steels. The first as a product of the cold-rolling forming (UOE) process also known as seam weld pipes and the second as a result of high temperature piercing process called seamless tube manufacturing. The experimental settings consist of a wide range of sample types, whose geometric characteristics represent different state of stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 40 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…As a noteworthy characteristic, many of these state-of-the-art ductile damage models assume a cut-off value [27] of stress triaxiality of -0.33 below which failure strain is infinite, which has been based on experimental results of round bar compression tests. Additionally, the nature of the loading (proportional or not) also influences the ductile damage significantly [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…As a noteworthy characteristic, many of these state-of-the-art ductile damage models assume a cut-off value [27] of stress triaxiality of -0.33 below which failure strain is infinite, which has been based on experimental results of round bar compression tests. Additionally, the nature of the loading (proportional or not) also influences the ductile damage significantly [28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The constitutive behavior of high silicon steel is expressed in a combination of exponential form and power law form. Paredes [17] reported that the predicted stressstrain behavior after yield as well as after strain localization was consistent with measurements when the Swift model [18] and Voce model [19] were properly combined, as shown in Equation ( 1):…”
Section: Stress-strain Behavior Of High Silicon Steelmentioning
confidence: 55%
“…The eight parameters (K, n, C η , η 0 , C s θ , C ax θ , C 1 , and C 2 ) must be calibrated for the construction of the fracture envelope from the MMC criterion. K and n are the same material constants adjusted for the power law (σ = Kε n ) [17]. C η and η 0 are the parameters that determine the yield criterion.…”
Section: D Fracture Locusmentioning
confidence: 99%
“…In order to characterize API S-135 failure in different stress states, several specimens were manufactured from a 5.5'' 21.9 ppf pipe (Figure 35). The extraction of the specimens for mechanical tests followed the procedure described by Paredes (2018) [89], which is illustrated in Figure 36.…”
Section: Mechanical Testingmentioning
confidence: 99%